Effect of Fungi Isolated from the Chenopodiaceae Family on the Growth Characteristics and Increasing Phosphorus Absorption of Barley (Hordeum vulgare) Plant - A Sadeghi; M Farsi; P Taheri; A. A Safari Sinegani (پژوهشهای زراعی ایران)
IntroductionPlant endophytes are microorganisms that live in healthy plant organs but do not cause disease symptoms, and the endophyte lifestyle plays an important role in plant growth, fitness, and diversity. Dark septate endophytic are a group of endophytic fungi that have special hyphae that form dark colonies in agar culture. In this stuy, the effect of these fungi on germination indicators, growth characteristics and increasing the amount of phosphorus in barley (Hordeum vulgare) plants was investigated, in order to investigate the possibility of using these fungi as biofertilizers in laboratory and greenhouse conditions.Materials and MethodsIn this study, seven endogenous fungal isolates were obtained from plants belonging to the Chenopodiaceae family including Aspergillus terreus, Penicillium sp., Curvularia spicifera, Alternaria alternaria, Fusarium solani, Fusarium brachigibbosum and Acremonium consortialis, which were identified in previous researches, were investigated. Piriformospora indica was used as a known fungal species. Yousef cultivar barley seeds were obtained from Khorasan Razavi Agricultural Research Center. The experiments were carried out as a completely randomized design with four replications in two sections: germination in the laboratory and planting in pots at the greenhouse of the faculty of agriculture of Ferdowsi university. To check the germination indicators, the seeds were stored on moist paper towels inside a sterile petri dish for one week at 28°C in an incubator. Sterile distilled water was used as control. After one week, germination speed, germination percentage, germination value, and vigor index were assessed. For the greenhouse study, the soil mixture (three parts sand and one part soil) was sterilized at 105°C for 48 hours. Pots measuring 20 x 20 cm were used. Seed inoculation was performed in a manner consistent with the germination test. Twelve seeds were sown in each pot, and at the two-leaf stage, the seedlings were thinned to eight plants per pot. After 28 days, the plants were evaluated for leaf area index, chlorophyll content, shoot phosphorus levels, dry weight, and fungal colonization percentage in the roots. Results and DiscussionThe percentage of colonization in all fungi except A. alternaria (%19.60) was above %30. The germination rate in the treatment with A. terreus (2.95 seed day-1) was significantly higher than the control and other fungi. Also, the germinationn rate in the treatment with A. alternaria, C. spicifera, A. consortialis, F. brachibosum and Penicilium sp. was more than control. Germination percentage in A. terreus (%95), Penicillium sp. (%90), C. spicifera (%85) and A. alternaria (%80) were higher than the control (α=%5). Considering that the viability of the selected seeds was low (control germination percentage %50) and the mentioned fungi were able to increase the germination percentage in these seeds, these fungi are a suitable option for sowing seeds with low germination percentage. The value of germination in the treatment with A. terreus (3.735) was higher than the control and other treatments. Treatment with Penicillium sp., A. alternaria and C. spicifera fungi was more than the control. The vigour index of treatment with A. terreus (13.65), C. spicifera (13.23) and A. alternaria (11.53) in one group and at a significant level of %5 were higher than treatment with other fungi. A. terreus treatment improved all germination indices and this increase was higher than the control species (P. indica). The amount of leaf phosphorus in the treatment with A. terreus (%0.516) and P. indica (%0.499) was higher than other fungal and control treatments. The leaf surface area in the treatment with A. terreus (9.97 cm2) was higher than the treatment with other fungi and the control fungus (9.84 cm2). In addition to A. terreus, the treatment with A. consortialis (10.06 cm2), C. spicifera (9.91 cm2) and P. indica (9.84cm2) was significantly higher than the control . Chlorophyll a and b were the highest in the treatment with A. terreus and P.indica. In addition, the treatment with C. spicifera and A. alternaria had more chlorophyll a and b at a significant level of 5% than the control treatment . The dry weight of shoot with the treatment of A. terreus (6.40 mg g-1) and P. indica (6.10 mg g-1) increased the most compared to the treatment with other fungi. ConclusionConsidering the ability of A. terreus in improving the germination characteristics, the plant growth conditions observed in this study. It is suggested to the next works should pay attention to the effect of this fungi on the environment and the ecosystem of other organisms and plants so that it can be used as a biological fertilizer. AcknowledgementWe thank ferdowsi university of mashhad for providing the necessary facilities for the implementation of the project, Ferdowsi University Department of Plant Medicine and Soil Science for providing the control strain and the necessary equipment, and the expert on breeding barley cultivars at Khorasan Razavi Agricultural and Natural Resources Research Center.